Endo-extra laryngeal suture: Indications, technique and results - Beyond laryngeal paralysis - Bernardo, Teresa (2014)
The reversible endo-extralaryngeal suture (REELS) is a surgical technique that allows increasing the glottal lumen. The authors present the Service´s experience with regard to indications, technique and results of REELS based on a retrospective study. We describe 10 patients, all female, seven with bilateral vocal fold paralysis (BVFP) after total thyroidectomy, two with laryngeal respiratory dystonia (LRD) and one with glottic stenosis (GS) due radiotherapy for glottic carcinoma. The ventilation improvement was immediate in all patients. Voice quality worsened initially but gradually recovered for most of them. We did not observe any choking or aspiration episodes. The REELS has good results for BVFP and in patients with LRD and GS.